PEMBUATAN LULUR KRIM DARI LIMBAH KULIT BAWANG MERAH (Allium cepa L) DAN CANGKANG TELUR AYAM DENGAN EMULGATOR SPAN-TWEEN 80 - Rina Kurniaty; Nadira Dina Mahyuna (Jurnal Insan Farmasi Indonesia, 2020)
Cream scrub is a body scrub that contains slightly harsh ingredients with cream-based ingredients. In this study, onion extract (Allium cepa L.) and chicken eggshell powder were used in order to determine which emulgator concentration (Span-Tween 80) could provide the best stability of cream scrub. Onion extract was made by maceration using methanol solvent to obtain liquid extract, afterward concentrated using vacuum rotary evaporator until a thick extract was obtained. There were 3 concentration variation of emulgator used for each 100 g of cream scrub formulation, namely 1% (F1), 2% (F2), and 3% (F3). Evaluation of cream scrub included organoleptic test, homogeneity test, dispersion test, emulsion type test and pH measurement. The results showed that all three cream scrub formulations were homogeneous and the cream scrub had M/A emulsion type. The results of dispersion test showed that F2 cream scrub had greater dispersibility than F1 and F3. Emulgator span-tween 80 with a concentration of 2% provided the best stability for cream scrub formulations.